PSYCHOPEDAGOGICAL INTERVENTION IN LEARNING DIFFICULTIES: A PRACTICAL ANALYSIS - Fernandes, Elisângela da Silva; Carvalho, Shirley Martins de Oliveira (Seven Editora, 2025)
This article is a synthesis of a psycho-pedagogical follow-up with a second-grade elementary school student experiencing learning difficulties. The psycho-pedagogical assessment process aims to gather data about the student’s life, analyzing their relationships with family and learning to understand the causes of the symptoms and factors maintaining the complaint, as well as to classify diagnostic instruments based on the reported complaint in order to intervene with the student and reverse their current situation. To this end, the contributions of several theorists were used as a foundation, such as: Acampora (2012), Bossa (2011), Fonseca (2009), Paín (1985), Sampaio (2011), Wallon (1992), among others. This work is structured as a case study and presents a concise conceptualization of the learning process, how it occurs in the individual, learning difficulties and their indicators as presented by the learner, aiming to intervene so that the child recovers their full potential to learn, as well as to restore and strengthen their self-esteem. DOI: https://doi.org/10.56238/sevened2025.038-024